BULLYING PRACTICES IN THE SCHOOL ENVIRONMENT - Prasitya, Ahmad Padli; Nining Surya Ningsih; Fadhilatillaili Arianingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The school environment plays a crucial role in student development, both in interacting with peers and creating a conducive learning atmosphere. However, field realities indicate that bullying disrupts the school environment, hinders the learning process, and threatens student well-being. The research utilises a literature review to explore bullying in elementary schools, including its impacts. For example, Kim et al. (2011) found a correlation between childhood bullying and later adolescent violence. Data from KPAI and FSGI highlight high bullying cases. It is expected to provide a deep understanding of this phenomenon and effective prevention strategies, potentially refreshing existing literature. The study results indicate that based on findings from various previous studies, factors such as personality, family environment, and school environment contribute to the occurrence of bullying behaviour. This behaviour has serious impacts, not only on victims physically and psychologically but also on their academic achievement and social well-being. To prevent and address bullying, schools need to implement effective strategies such as bullying prevention socialization, counseling services for victims and perpetrators, character education, and practising religious values. Thus, a comprehensive understanding of the bullying phenomenon and the implementation of appropriate strategies are expected to create a safe, comfortable, and conducive school environment for optimal student development